(3GdOQQ GdZQhjI aj eOGFM heQGKj GdYJQI GdeUWahjIs - (3UGdM Hf egOj Hf QVG Hf eMeO Ydj GdMSjfj GdbRhjfj GdHZOGOjs ((3eMeO WGgQ GdSeGhj s)
(3ChdgG (B:s
(3hHYO(B: (3ajbhd Efj efP YdbJ CfGedj HCgOGH Yjhf GdBOGH hhUd Edi eG GfJgi dehGdjfG GdCFeI GdCWjGH ef TOjO GdeUGH s
(3BNQgG (B:s
(3ef GdbUjOI GdQGHYI YTQI bhdg(B: (3dce GdSdGe eNdO eG fGdJ GdCTjGY aj OGQ GdSdGe NdhOkG hYdjce Udi Gdegjef cdeG gR GdUHG ZV GdfbG GdCedhOG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B198 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B13s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B4 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs